2020
DOI: 10.1016/j.jaci.2019.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Rapid desensitization of humanized mice with anti-human FcεRIα monoclonal antibodies

Abstract: Background: Anaphylaxis is classically mediated by allergen cross-linking of IgE bound to the a chain of FcεRI, the mast cell/basophil high affinity IgE receptor. Allergen cross-linking of the IgE/FcεRI complex activates these cells, inducing release of disease-causing mediators, cytokines, and enzymes. We previously demonstrated that IgE-mediated anaphylaxis could be safely prevented in wild-type BALB/c mice by rapid desensitization with anti-mouse FcεRIa mAb. Objective: This study sought to use humanized mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 61 publications
0
30
0
Order By: Relevance
“…[126][127][128] "Humanized" mice are defined here as immunodeficient mice (SCID) that are xenotransplanted with relevant functional human biological systems, as opposed to "fully humanized" mice whose hematopoietic system has been reconstituted by a human one after mouse bone marrow radioablation. 129 While a humanized AD mouse model using human skin transplants has not yet been published, a very interesting humanized mouse model for acute human AD has recently been presented. This uses an in vitro-generated and transplanted human skin "equivalent" that is repetitively injected intradermally with Th2-polarized human CD4+ T lymphocytes over two weeks after partial removal of stratum corneum by tape-stripping.…”
Section: Humanized Mouse Model For Acute Admentioning
confidence: 99%
See 1 more Smart Citation
“…[126][127][128] "Humanized" mice are defined here as immunodeficient mice (SCID) that are xenotransplanted with relevant functional human biological systems, as opposed to "fully humanized" mice whose hematopoietic system has been reconstituted by a human one after mouse bone marrow radioablation. 129 While a humanized AD mouse model using human skin transplants has not yet been published, a very interesting humanized mouse model for acute human AD has recently been presented. This uses an in vitro-generated and transplanted human skin "equivalent" that is repetitively injected intradermally with Th2-polarized human CD4+ T lymphocytes over two weeks after partial removal of stratum corneum by tape-stripping.…”
Section: Humanized Mouse Model For Acute Admentioning
confidence: 99%
“…Since none of the mouse “AD” models discussed above convincingly mimics enough of the relevant characteristics of human AD (Table 2), investigators have turned to so‐called “humanized” mice as being increasingly important in vivo models for the preclinical study of human skin pathology, including psoriasis and alopecia areata (Text ) 126‐128 . “Humanized” mice are defined here as immunodeficient mice (SCID) that are xenotransplanted with relevant functional human biological systems, as opposed to “fully humanized” mice whose hematopoietic system has been reconstituted by a human one after mouse bone marrow radioablation 129 …”
Section: Currently Available “Ad” Animal Modelsmentioning
confidence: 99%
“…[11][12][13][14] During the past few years, we have used conventional, then humanized mouse models to study the feasibility of using a rapid desensitization approach that replaces a single allergen with a mAb to FcεRIa (the IgE-binding chain of the FcεRI heterotetramer 15 ), with the goal of suppressing all IgE-mediated allergy rather than only disease caused by the single allergen. 12,16 Our studies have demonstrated the feasibility and efficacy of this approach, which, in addition to suppressing all IgE-mediated anaphylaxis was safer and longer lasting in our models than allergen-mediated desensitization was. 12 However, we also found that an extended period of treatment with very slow increases in anti-FcεRIa mAb dose was required to desensitize mice that were particularly susceptible to anaphylaxis.…”
mentioning
confidence: 72%
“…BALB/c background huFcεRIa mice, which lack mouse FcεRIa and express transgenic huFcεRIa, and huFcεRIa/F709 mice, which additionally express IL-4Ra with a mutation (F709) that allows only positive signaling by IL-4 and IL-13, were bred as previously described. [16][17][18] These mice, unlike otherwise identical mice that lack the IL-4Ra F709 mutation, develop egg allergy in response to epicutaneous treatment, followed by oral gavage (og) with egg. 16 Human IL-3/SCF/GM-CSF transgenic, immune-deficient NOD/ LtSz-severe combined immunodeficiency IL-2RG 2/2 (NSGS) or NOD/ Rag1 2/2 /IL-2RG 2/2 mice were bred at a Cincinnati Children's Hospital Medical Center core and engrafted with T cell-depleted human cord blood cells as previously described.…”
Section: Methods Micementioning
confidence: 99%
See 1 more Smart Citation